Bridging capability gaps in technology transfers within related offsets. Issue 5 (6th June 2016) - Malm, Anna Margaretha; Fredriksson, Anna; Johansen, Kerstin
Abstract : Purpose: – The purpose of this paper is to explore how capability gaps can be identified and how they can be dealt with in aircraft technology transfers in future offset deals. Design/methodology/approach: – The study is based on lessons learned as identified from three case studies of technology transfers from Saab, a Swedish aircraft manufacturing company to South Africa, the Czech Republic, and India. Findings: – The capability gap between sender and receiver has to be dealt with on two levels: on an organizational level; and on an individual level. It is proposed that the disseminative capacity constitutes the ability to assess the capability gap between the sender and receiver, and to convert this assessment to adaptations of the product and production process to include in an industrialization process. On the individual level, the capability-raising activities were connected to employees' knowledge, personal development plans for the transfer of explicit knowledge, as well as on-the-job training to facilitate the exchange of tacit knowledge. Research limitations/implications: – The research is based on case studies from one company. Therefore, it is necessary to confirm the proposed propositions through new case studies in other contexts as well as through survey-based research. Originality/value: – The paper focusses on the context of offset and reports on actual experiences from a capability perspective of technology transfers within the aircraft manufacturing area. It proposes a structured way of identifying and bridging the capability gap within such transfers.